EVALUASI PRAKTIKUM BOTANY PHANEROGAMAE DENGAN MENGGUNAKAN MODEL CSE-UCLA (Studi pada Mahasiswa Jurusan Tadris Biologi Institut Agama Islam Negeri Kerinci) - Emayulia Sastria; Novinovrita .; Arif Maulana; Devie Novalyan (Jurnal Biotek, 2018)
One of the ways to maximize the practicum function carried out in lectures is through the evaluation of practicum programs. So far there has never been an evaluation on practicum, which only focuses on the implementation of the practicum itself. There are many program evaluation models designed by experts. These models tend to be developed in accordance with the objectives of evaluation. One of them is the CSE program evaluation model UCLA. This study aims to find out assessment systems, program planning, implementation programs and certification certification programs Botany phanerogamae students majoring in biology IAIN Kerinci. This research belongs to the category of qualitative research which includes the type of case study method (case study). To get the CSE-UCLA model data, researchers used observational studies, documents and interviews. At the stage of the assessment assessment system has been owned and implemented, although there are obstacles to the lack of student attention to the environment. At the planning stage, the program focuses on evaluating the feasibility of the organizational structure of the Department of Biology, evaluating the readiness of the ability of lecturers and assistants, advice and infrastructure and labor managers in the Botany Phanerogamae Practicum which is categorized ready. In the Implementation Program stage it has been carried out well and also structured. The Improvement Program has been categorized as effective. In the Certification Program stage it is in accordance with the wishes of the Department of Biology. Where the practicum objectives and responses of the students are very positive, so that the stages of practicum implementation can run effectively and in accordance with the expected desires of the Department of Biology of the Kerinci Islamic Institute. Keywords: System assessment, program planning, implementation programs, program certification and Botanical phanerogamae.